1992
DOI: 10.1002/1097-4679(199207)48:4<500::aid-jclp2270480410>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Ego-strength revised:A comparison of the MMPI-2 and MMPI-1 versions of the barron Ego-strength scale

Abstract: This study evaluated the equivalence of the original MMPI and the shortened MMPI‐2 versions of the Barron (1953) Ego‐strength scale, an important research scale. Three hundred fifty‐five subjects took the MMPI‐2 and the 16 MMPI‐1 items dropped from the original scale. The omitted items appear to contribute little to the original scale. The revised version compares favorably with the old in terms of internal consistency, and the two versions are highly intercorrelated. Confirmatory Factor Analysis indicates tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…The scale has demonstrated good reliability (alpha=0.66) [40], also in this study (alpha=0.70). Emotional and tangible support from networks was measured using the Norbeck Social Support Questionnaire (NSSQ).…”
Section: Methodssupporting
confidence: 61%
“…The scale has demonstrated good reliability (alpha=0.66) [40], also in this study (alpha=0.70). Emotional and tangible support from networks was measured using the Norbeck Social Support Questionnaire (NSSQ).…”
Section: Methodssupporting
confidence: 61%
“…One study employed a conceptual framework, specifically Ferrell and Grant's Quality of Life Model [18, 19]. All studies employed a range of validated HRQOL measurement tools, including the Psychological Adjustment to Illness Scale [48], Interpersonal Support Evaluation List [49], Quality of Life/Breast Cancer Psychological Well-Being Subscale [18, 19], Functional Assessment of Cancer Therapy-Breast [50], Quality of Life in Adult Cancer Survivors [51], Beck Depression Inventory-Short Form [52], and Barron's Ego Strength Scale [53]. All studies met 50 % of the critical appraisal criteria, and five studies met over 70 % of appraisal criteria.…”
Section: Resultsmentioning
confidence: 99%
“…The Ego Strength scale was originally developed to predict individual psychotherapy outcome, with higher scores on this scale indicating a higher level of adjustment and lower scores indicating a higher level of maladjustment. Subsequent research has also revealed that the ES scale is related to the presence of psychological resources needed for day‐to‐day functioning (e.g., Archer, Elkins, Aiduk, & Griffin, 1997; Schuldberg, 1992). Further, Graham (2000a) has cited research data showing that the ES indicates overall psychological adjustment, as assessed concurrently by other MMPI‐2 indexes and extra criteria.…”
Section: Methodsmentioning
confidence: 99%